Investigation of genetic variants, birthweight and hypothalamic-pituitary- adrenal axis function suggests a genetic variant in the SERPINA6 gene is associated with corticosteroid binding globulin in the Western Australia Pregnancy Cohort (Raine) study - Anderson, L.; Briollais, L.; Atkinson, Helen; Marsh, J.; Xu, J.; Connor, K.; Matthews, S.; Pennell, C.; Lye, S. (Public Library of Science, 2014)
Background: The hypothalamic-pituitary-adrenal (HPA) axis regulates stress responses and HPA dysfunction has been associated with several chronic diseases. Low birthweight may be associated with HPA dysfunction in later life, yet human studies are inconclusive. The primary study aim was to identify genetic variants associated with HPA axis function. A secondary aim was to evaluate if these variants modify the association between birthweight and HPA axis function in adolescents. Methods: Morning fasted blood samples were collected from children of the Western Australia Pregnancy Cohort (Raine) at age 17 (n = 1077). Basal HPA axis function was assessed by total cortisol, corticosteroid binding globulin (CBG), and adrenocorticotropic hormone (ACTH). The associations between 124 tag single nucleotide polymorphisms (SNPs) within 16 HPA pathway candidate genes and each hormone were evaluated using multivariate linear regression and penalized linear regression analysis using the HyperLasso method. Results: The penalized regression analysis revealed one candidate gene SNP, rs11621961 in the CBG encoding gene (SERPINA6), significantly associated with total cortisol and CBG. No other candidate gene SNPs were significant after applying the penalty or adjusting for multiple comparisons; however, several SNPs approached significance. For example, rs907621 (p = 0.002) and rs3846326 (p = 0.003) in the mineralocorticoid receptor gene (NR3C2) were associated with ACTH and SERPINA6 SNPs rs941601 (p = 0.004) and rs11622665 (p = 0.008), were associated with CBG. To further investigate our findings for SERPINA6, rare and common SNPs in the gene were imputed from the 1,000 genomes data and 8 SNPs across the gene were significantly associated with CBG levels after adjustment for multiple comparisons. Birthweight was not associated with any HPA outcome, and none of the gene-birthweight interactions were significant after adjustment for multiple comparisons. Conclusions: Our study suggests that genetic variation in the SERPINA6 gene may be associated with altered CBG levels during adolescence. Replication of these findings is required. © 2014 Anderson et al.